Manajemen Organisasi PAUD Berbasis Pendekatan Emosional dalam Meningkatkan Kenyamanan Belajar Anak - Laylatul Fatlia; Dea Najwa Azzahra; Nurhasanah Sigalingging; Kasman Kasman (CV. Alim's Publishing, 2026)
This study aims to analyze the implementation of emotional approach-based organizational management in Early Childhood Education (PAUD) in improving children's learning comfort. The emotional approach in PAUD organizational management is an important strategy in creating a safe, enjoyable, and supportive learning environment for children's social and emotional development. This research used a qualitative method with a descriptive approach. Data collection techniques were carried out through observations, interviews, and documentation involving principals, teachers, and students in PAUD institutions. The results showed that the implementation of an emotional approach in PAUD organizational management could improve children's learning comfort through warm communication between teachers and students, child-friendly classroom management, positive motivation, and good collaboration between schools and parents. In addition, the emotional approach helps children become more confident, active, and socially interactive. Therefore, emotional approach-based organizational management in PAUD plays an important role in creating a conducive learning atmosphere and supporting the optimal development of early childhood learners.